Teachers’ narratives of pedagogical practices: To educate for democratic peace in Egypt and in Canada - Awad, Y. (South African Journal of Higher Education, 2020)
Education for democratic peacebuilding citizenship includes four essential components: handling conflict, practising dialogue, recognizing diversity, and building a pedagogical community. Teachers can help one another to interpret, to learn, and to implement these pedagogical practice dimensions, in order to equip their students with democratic agency and values to participate in peacebuilding social change. This comparative case study research examines how two groups of private school teachers ‒ four in the Greater Cairo area and three in the Greater Toronto area ‒voluntarily embarked on two journeys of non-formal professional learning to improve their teaching for democratic peace. The researcher developed and facilitated a six-session collaborative, reflective dialogic professional learning course for democratic peacebuilding, and studied each group of teachers’ pedagogical practices.